Deciphering 40 TeV rapidity gap physics with 2 TeV jet events - Chehime, H.; Gay Ducati, M. B.; Duff, A.; Halzen, F.; Natale, A. A. [UNESP]; Stelzer, T.; Zeppenfeld, D. (Elsevier B.V., 1992)
Rapidity gaps may provide an adequate signature for electroweak processes at supercolliders, including the production of the Higgs particle. We show how this important issue can be studied in the dijet final states of operating proton-antiproton colliders and present quantitative predictions.